Brockers and bridges: Social networks as drivers of Tanzania rural business development - Nyaki, Stephen A.; Kilima, Fredy T.M.; Larsen, Marianne N.; Bahta, Yonas T. (South African journal of economic and management sciences, 2025)
Background: Small businesses drive rural transformation in Africa; however, their potential is hindered by limited access to essential resources. In Tanzania’s emerging urban centres (EUCs), where agrarian and urban economies intersect, social networks’ role in business development has received limited empirical attention. Aim: This study examined how strong and weak social networks of family, friends, and businesses influence small business performance in rural Tanzania. Setting: This study was conducted in Ilula, a small town in the Kilolo district of the rural Iringa region, Tanzania. Method: Gephi Geolayout and ordinary least squares (OLS) regression were used to plot social networks and examine their influence on business performance from a random sample of 459 businesses. Results: Social networks influenced the vertical and horizontal flow of products and information. Businesses linked to dominant tomato value chains and manufacturing and wholesale retail trading are central network brokers and bridges of information and products. However, institutions as enablers played a limited role in supporting networking. The OLS results showed that increasing business network size and social influence enhanced business performance. Conclusion: The interaction of businesses in EUCs provides social interaction supporting market information and goods flow, furthering business development. Networks can expand through institutions, enabling resource pooling. Contribution: Leveraging EUCs’ geographical potential along the rural-urban continuum, strengthening social networks among business subgroups while providing supportive structures like institutions, road infrastructure, finance and capacitation to businesses, especially those linked with key crop value chains, will enhance business performance and rural development.